Estratégias para o enriquecimento de áreas ripárias em processo de restauração no extremo sul do bioma Mata Atlântica - Griebeler, Adriana Maria (2019)
The general objective of this research was to characterize the development of native forest species in the enrichment of restoration riparian areas, introduced through direct seeding and seedlings planting, in order to define effective strategies for the enrichment of areas in the southern extreme of the Atlantic Forest Biome. From this, an area in the initial restoration process implemented in 2013 was used for the preparation of the present dissertation, which was structured in two chapters. In chapter I, the objective was to evaluate the efficiency of the technique of direct seeding of native forest species and the influence of the use of Trichoderma asperelloides and water-retaining polymer as strategies for the enrichment of area in the initial process of restoration (four years), in the Southern extreme Atlantic Forest Biome. The species used were Balfourodendron riedelianum (Engl.) Engl, Cedrela fissilis Vellozo, Luehea divaricata Mart. & Zucc, Enterolobium contortisiliquum (Vell.) Morong and Parapiptadenia rigida (Benth.) Brenan. The experiment was conducted in a 2 x 2 factorial scheme, considering seed inoculation with Trichoderma spp. (T. asperelloides and control) and the presence or absence of hydrogel in the pit. In September 2017, direct seeding was done in the field, as well as the installation of emergency test in nursery. The emergence (E%) was evaluated for 150 days and the survival (S%), growth in height (H) and stem diameter (SD) at 12 months after sowing. It was verified that in nursery conditions, the inoculation and the use of hydrogel did not influence the E% of the species tested. In the field, E. contortisiliqumm, P. rigida and C. fissilis are suitable for use in enrichment direct seeding. In addition, the use of T. asperelloides proved to be an efficient strategy to potentiate the results of direct sowing, capable of providing greater E% for E. contortisiliqumm and P. rigida, as well as maximizing the height growth of E. contortisiliqumm. Complementarily, under high rainfall intensity, the use of hydrogel does not influence the emergence and morphological attributes of the studied species and should be dispensed. In Chapter II, it was aimed to characterize the performance of five native tree species in an enrichment planting at the southern end of the Atlantic Forest Biome, as well as to identify the influence of the substrate volume used in seedling production and the inoculation of Trichoderma spp. in survival, initial growth and physiological aspects of planted species. The species studied were Cabralea canjerana (Vell.) Mart., Cedrela fissilis Vellozo, Cordia trichotoma (Vell.) Arráb. ex Steud, Erythrina cristagalli L. and Luehea divaricata Mart. & Zucc. The experiment was conducted in a 2 x 3 factorial scheme, considering two types of containers (polypropylene tubes and polyethylene bag), and the inoculums tested (T. asperelloides, Trichoderma harzianum and control). The planting occurred in September 2017. Six months after planting, physiological attributes were evaluated, and at 15 months at S%, morphological attributes and the tolerance and resilience of the species to frost. It was verified that the five species studied presented satisfactory S% and growth, being able to compose enrichment plantations. However, frost formation reduces the performance potential of C. trichotoma, C. canjerana and E. cristagalli. In general, the survival and morphophysiological aspects of the evaluated species were not influenced by the type of container, being indicated the use of seedlings produced in tubes of 180 cm³. The use of T. asperelloides provides improvements on the growth and physiological aspects of C. canjerana, C. fissilis and C. trichotoma, proving to be a potential strategy to improve plant performance.